2017
DOI: 10.1002/cncr.30935
|View full text |Cite
|
Sign up to set email alerts
|

Strategic recruitment of an ethnically diverse cohort of overweight survivors of breast cancer with lymphedema

Abstract: BACKGROUND: Black women are more likely to experience adverse effects from cancer treatment such as lymphedema. Thus, black women may particularly benefit from research regarding interventions to improve lymphedema. Herein, the authors report the challenges and strategies related to the recruitment of minority survivors of breast cancer and to the recruitment of survivors of breast cancer with lymphedema into the Women In Steady Exercise Research (WISER) Survivor Clinical Trial. METHODS: Subjects for this comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 36 publications
2
29
0
Order By: Relevance
“…We found that the representation of blacks among RCT participants has decreased since 2006-2011 in the USA, which is consistent with reviews of race/ethnic representation in other disease states [16]. Reasons for minority under-representation in RCTs are multifactorial and often involve system-level actors-e.g, clinicians, hospitals, and the community [21][22][23][24]. Historical acts of discrimination and marginalization in healthcare settings (e.g., the Tuskegee Syphilis Study) have been hypothesized as reasons why racial minorities are more distrustful of health systems and may also contribute to the under-representation of these groups in RCTs.…”
Section: Discussionsupporting
confidence: 82%
“…We found that the representation of blacks among RCT participants has decreased since 2006-2011 in the USA, which is consistent with reviews of race/ethnic representation in other disease states [16]. Reasons for minority under-representation in RCTs are multifactorial and often involve system-level actors-e.g, clinicians, hospitals, and the community [21][22][23][24]. Historical acts of discrimination and marginalization in healthcare settings (e.g., the Tuskegee Syphilis Study) have been hypothesized as reasons why racial minorities are more distrustful of health systems and may also contribute to the under-representation of these groups in RCTs.…”
Section: Discussionsupporting
confidence: 82%
“…Recruitment strategies were targeted to increase the participation of racial/ethnic minorities as described earlier [31]. Over a 39-month period, participants were recruited through both active strategies such as community education events supplemented and passive approaches, such as mailings to survivors identified through hospital and state cancer registries.…”
Section: Methodsmentioning
confidence: 99%
“…Monthly in-person sessions consisted of a meeting with the fitness professional to address questions and concerns, and to provide behavioral counseling to improve intervention adherence and exercise-related behavior. According to the preference of the participants, they did their weight training in their homes or in a community gym facility except for the first six weekly sessions and monthly check-in sessions which were completed at the intervention site closest to the participant’s home [31]. …”
Section: Methodsmentioning
confidence: 99%
“…These recruitment rates are similar to what was reported previously in other behavioral lifestyle trials involving a substantive percentage of minorities. For example, in the Women in Steady Exercise trial (http://ClinicalTrials.gov identifier NCT01515124), letters sent to women using state and hospital registries resulted in a 0.4% recruitment (randomization) rate; however, their education and recruitment sessions that led to direct referrals yielded a 10% success in recruitment rate 20 . Greenlee et al 3 reported an approximately 37% recruitment rate (42 of 112 screened participants) in a pilot study involving Hispanics and AAs conducted at Curves facilities, but their primary recruitment strategy was through direct referrals.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is of paramount interest to understand the barriers to minority recruitment and retention in cancer clinical trials and to identify recruitment and retention strategies to improve trial participation. Previously reported barriers to the recruitment of minority breast cancer survivors to intervention studies include distrust of research and the health care system, work constraints, transportation issues, low literacy, language barriers, and a negative perception of diet and exercise 13,20 …”
Section: Introductionmentioning
confidence: 99%